Pengaruh Budaya, Agama dan Pendidikan Terhadap Tren Pernikahan Dini Masyarakat Kampung Nelayan - Maisarah; Mailita; Fenny Rahmasari; Haidil Mahindra (Fakultas Agama Islam Universitas Billfath, 2024)
Early marriage is one of the highest social problems in Indonesia, and places Indonesia in the 10 countries in the world with the highest cases of child marriage. The aim of this research is to determine the influence of culture, religion and education on the trend of early marriage in fishing village communities in Bumi Makmur District, Tanah Laut Regency, South Kalimantan Province. The methods used in this research are descriptive qualitative and quantitative (mixed methods). Data collection techniques used were observation, interviews, documentation and questionnaires. The results of this research, early marriages occurring in Bumi Makmur District are currently registered and there have been 15 early marriages recorded since 2018-2023, indeed not many have registered their marriages with the Office of Religious Affairs due to the minimum marriage age requirement based on the applicable law. , the age of the prospective groom and bride must be at least 19 years old at the time of the wedding. As for those who register their marriage at the Religious Affairs Office even though their age does not meet the requirements, provided that they have applied for a dispensation permit and based on the decision of the religious court. Based on the results of the variable significance test, it is known that there is a significant influence and relationship between the variables culture (X1) and education (X2) on the decision to marry underage or old enough. However, there is no significant relationship between religion and the decision to marry underage or old enough in the fishing village community of Bumi Makmur District. Furthermore, the effect shows an r_phi of 0.1239, indicating a moderate relationship between the decision to marry underage or old enough and education. Because χ^2=3.919>3.841. This means that based on the respondents' answers, there is a significant relationship between education and the decision to marry underage or old age.